The Roles of Institutional Investors and Insiders in Earnings Management Around IPO Firms in Taiwan - Hsu, Ming-Feng; Wen, Shiow-Ying (International Journal of Economics and Financial Issues, 2015)
This paper examines the influence of the proportion and stability of insider’s and institutional shareholdings on earnings management after initial public offerings (IPOs) firms in Taiwan, covering data in Taiwan Stock Exchange and GreTai Securities Market from 2000 to 2009. We apply performance-matched discretionary accruals and performance-matched real earnings management as dependent variables to depicting earnings management behavior. The empirical findings show that managers with unstable high shareholdings tend to perform accruals management to fit the threshold in the second year and the third year after IPOs. Further, institutional investors with unstable high shareholdings incline to courage firms to manipulate discretionary accruals for short-term trading profits in all three years after IPOs. Keywords: Insiders; Institutional investors; Earnings management; IPO JEL Classifications: G34; M41